Marine Biosecurity Crisis Decision-Making: Two Tools to Aid “Go”/“No Go” Decision-Making - Campbell, Marnie L.; Leonard, Kaeden; Primo, Carmen; Hewitt, Chad L. (Frontiers in Marine Science, 2018)
Determining if a marine species is introduced to an area is an important first step when considering if control or eradication should be attempted. This step is often challenging, especially when data and introduced species expertise is limited: yet decisions about responding to a new invasion needs to occur in a timely manner. The crux is that biosecurity crisis decisions are often made in a vacuum. To improve this process, we outline a rapid response approach that uses a non-probabilistic decision tree to direct decision makers, with additional criteria to determine if a species is native, cryptogenic or introduced. The expanded criteria were derived from patterns within a 10-year dataset of quantitative introduced marine species surveys and is compared against the original Chapman and Carlton 10-point criteria for identifying a species status. Effective use of the rapid response decision-tree and species criteria requires a multi-disciplinary approach drawing upon biology (taxonomy, phylogeny, genetics, ecology, biogeography) and monitoring. The criteria are evaluated against 213 bryozoan species present in Australian waters that were randomly selected from species present in the Australian port surveys and available in the scientific and grey literature. A multivariate evaluation highlighted that a weight of evidence using the expanded criteria approach was successful in determining if a species is introduced or native, and that a number of criteria may be rarely met but when they are met, they provide strong evidence that a species is introduced. The expanded criteria clearly differentiated introduced and cryptogenic species from native species and consequently would reduce mis-classifications of introduced species as native species (Type I error) in comparison to the original criteria. However, differentiating between introduced and cryptogenic species was problematic, especially when using the original criteria. Using both the rapid response decision tree and the criteria provides a quantifiable mechanism to aid decision-makers in deciding whether to respond to a marine species introduction.